Social Media Use Profile of Farmers in Haryana (Indian Journal of Extension Education, 2022)
Social media are digital networks that are used to share and discuss user generated informa tion - opinion, video, audio, and multimedia spreading far and wide even in remote areas of the country and has changed the way farmers communicate and interact. This study was conducted in 2021, with an objective to understand to understand the use of social media by farmers and to analyze its relationship with economic profile characteristic. The data were collected personally from Hisar and Sonipat districts of Haryana, with a sample size of 200 respondents comprising 25 farmers from eight villages through a structured interview sched ule. Findings revealed that 69.00 per cent of the respondents were in medium category of social media use. Garrett ranking analysis revealed that watching videos was the most pre ferred purpose of social media use among farmers followed by chatting/ connecting with peers. Also, YouTube was found to be most preferred social media followed by WhatsApp and Facebook. Further, education, family income, cosmopoliteness-localiteness, social par ticipation, extension contact and extension participation showed positive relationship with social media use while age had negative relationship. Also, regression analysis showed that the eleven personal variables selected for the study could explain 53.30 per cent variation in the social media use.